Evaluation of the effectiveness and cost-effectiveness of lightweight fibreglass heel casts in the management of ulcers of the heel in diabetes: a randomised controlled trial - Jeffcoate, William; Game, Frances; Turtle-Savage, Vivienne; Musgrove, Alison; Price, Patricia; Tan, Wei; Bradshaw, Lucy E.; Montgomery, Alan A.; Fitzsimmons, Deborah; Farr, Angela; Winfield, Thomas; Phillips, Ceri (NIHR Health Technology Assessment Programme, 2017)
Background Ulcers of the foot in people with diabetes mellitus are slow to heal and result in considerable cost and patient suffering. The prognosis is worst for ulcers of the heel. Objective To assess both the clinical effectiveness and the cost-effectiveness of lightweight fibreglass casts in the management of heel ulcers. Design A pragmatic, multicentre, parallel, observer-blinded randomised controlled trial. A central randomisation centre used a computer-generated random number sequence to allocate participants to groups. Setting Thirty-five specialist diabetic foot secondary care centres in the UK. Those recruited were aged ≥ 18 years and had diabetes mellitus complicated by ulcers of the heel of grades 2–4 on the National Pressure Ulcer Advisory Panel and European Pressure Ulcer Advisory Panel scale. Participants In total, 509 participants [68% male, 15% with type 1 diabetes mellitus, mean age 67.5 years (standard deviation 12.4 years)] were randomised 1 : 1 to the intervention (n = 256) or the control (n = 253) arm. The primary outcome data were available for 425 participants (212 from the intervention arm and 213 from the control arm) and exceeded the total required; attrition was 16.5%. The median ulcer area at baseline was 275 mm2 [interquartile range (IQR) 104–683 mm2] in the intervention group and 206 mm2 (IQR 77–649 mm2) in the control group. There were no differences between the two groups at baseline in any parameter, neither in relation to the participant nor in relation to their ulcer. Interventions The intervention group received usual care supplemented by the addition of an individually moulded, lightweight, fibreglass heel cast. The control group received usual care alone. The intervention phase continued either until the participant’s ulcer had healed (maintained for 28 days) or for 24 weeks, whichever occurred first. During this intervention phase, the participants were reviewed every 2 weeks, and the fibreglass casts were replaced when they were no longer usable. Main outcome measures The primary outcome measure was ulcer healing (confirmed by a blinded observer and maintained for 4 weeks) within 24 weeks. Other outcome measures included the time taken for the ulcer to heal, the percentage reduction in the cross-sectional area, the reduction in local pain, amputation, survival and health economic analysis. The study was powered to define a difference in healing of 15% (55% intervention vs. 40% control). Results Forty-four per cent (n = 94) of the intervention group healed within 24 weeks, compared with 37% (n = 80) of the control participants (odds ratio 1.42, 95% confidence interval 0.95 to 2.14; p = 0.088), using an intention-to-treat analysis. No differences were observed between the two groups for any secondary outcome. Limitations Although the component items of care were standardised, because this was a pragmatic trial, usual care was not uniform. There was some evidence of a small excess of adverse events in the intervention group; however, non-blinded observers documented these events. There was no excess of adverse device effects. Conclusions There may be a small increase in healing with the use of a heel cast, but the estimate was not sufficiently precise to provide strong evidence of an effect. There was no evidence of any subgroup in which the intervention appeared to be particularly effective. A health economic analysis suggested that it is unlikely that the intervention represents good value for money. The provision of a lightweight heel cast may be of benefit to some individuals, but we have found no evidence to justify the routine adoption of this in clinical practice. Future work It is unlikely that further study of this intervention will have an impact on usual clinical care, and so future efforts should be directed towards other interventions designed to improve the healing of ulcers in this population.